Pengembangan Media “Rahayuning Bawana” untuk Meningkatkan Kemampuan Motorik Peserta Didik dalam Pembelajaran Seni Tari - Dina Nur Karochmah; Rana Gustian Nugraha; Aah Ahmad Syahid (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The aim of this research is to produce the development of learning media in the form of an interactive flipbook, namely the "Rahayuning Bawana" media in order to improve students' motor skills in dance learning in elementary school extracurriculars. This research uses the research and development (RnD) method, and the model used is ADDIE, which consists of five stages: analysis, design, implementation, development, and evaluation (Analysis, Design, Development, Implementation, and Evaluation). The media "Rahayuning Bawana" has been validated by material experts and media experts. Material expert validation received a score of 93% and was categorized as very suitable for use. Meanwhile, media expert validation received a score of 87% and was categorized as very suitable for use as well. The subjects of this research involved extracurricular dance students at SDN Tanjungsari II and SDN Cileutik. Student responses to the media "Rahayuning Bawana" reached an average of 93%, with very good qualifications. The average pretest result was 34 and the average posttest result was 88.4 with an increase in n-gain of 0.82. Therefore, it can be concluded that the existence of the "Rahayuning Bawana" media is very feasible and effective for use in dance learning to improve students' motor skills.